Fabrication of 2D Metal–Organic Framework Nanosheets with Highly Colloidal Stability and High Yield through Coordination Modulation - Zhou, Huazhang; Zhang, Liying; Wang, Guizhou; Zhang, Yichi; Wang, Xuanhe; Li, Mengchu; Fan, Fuqiang; Li, Yunong; Wang, Tieqiang; Zhang, Xuemin; Fu, Yu (ACS applied materials & interfaces, 2021)
2D metal–organic frameworks (MOFs) are promising 2D materials with a wide range of applications due to their unique physical and chemical properties. However, 2D MOFs are prone to stacking due to their ultrathin thickness, and the high-yield preparation method of 2D MOFs is highly demanded. In this work, a rapid and scalable method is novelistically presented to prepare 2D MOFs with highly colloidal stability and high yield through coordination modulation at room temperature. A well-ordered CuBDC-MBA nanosheet (BDC, 1,4-benzenedicarboxylic; MBA, 4-methoxybenzoic acid) fabricated by introducing MBA as a modulator exhibits extremely stable colloid suspension for 6 months and the yield of well-dispersed CuBDC-MBA is higher than 88.6%. As MBA successfully participates in synthetic coordination of CuBDC-MBA and is presumably installed on the edge of 2D MOFs with low MBA content due to anisotropic growth, CuBDC-MBA and CuBDC are similar with respect to nanosheet morphology, integrated crystal structure, and porosity. Moreover, well-dispersed CuBDC-MBA shows higher catalytic effectiveness for the cycloaddition reaction of CO2 with 1.5 times higher yield than CuBDC. Thus, this method can provide a new idea based on coordination modulation to directly fabricate 2D MOFs with purposeful properties.